Artificial bee colony algorithm used for load balancing in cloud computing: review - Arif Ullah; Nazri Mohd Nawi; Jamal Uddin; Samad Baseer; Ansam Hadi Rashed (IAES International Journal of Artificial Intelligence (IJ-AI), 2019)
Cloud computing is emerging technology in IT land. But it still faces challenges like load balancing. It is a technique which dynamic distributed work load among various nodes equally in a situation where some nodes are under load and some are overload. Main achievements of load balancing are resource consumption and reduce energy. Swarm intelligence provides an important role in the field of those problems which cannot easily solve and they need classical and mathematical technique. An artificial bee colony is a foraging behavior inspires algorithm it established by karaboga in 2005. It has fast convergence, strong, robustness, and high flexibility. The different researcher used ABC algorithm for improvement in load balancing. This review paper is a comprehensive study about load balancing in cloud computing using ABC algorithm. It also defines some basic concept about swarm intelligent and its property.